Existence of solutions for an impulsive boundary value problem with nonlinear derivative dependence on unbounded intervals via variational methods - BOUMARAF, Sihem; MOUSSAOUI, Toufik (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we employ the critical point theory and iterative methods to establish the existence of solutions for an impulsive boundary value problem with nonlinear derivative dependence on the half-line. Mathematics Subject Classification (2010): 34B37, 34B40, 35A15, 47J25. Received 26 October 2019; Accepted 17 January 2020.